+0  
 
0
73
2
avatar+186 

Find p+q, given that (q+4)(p+3)-(q+2)(p+1)=44

 Aug 8, 2020
 #1
avatar
0

a=1; b=1;d=(b+4)*(a+3)-(b+2)*(a+1) ; if(d==44, goto4, goto5);printa, b; a++;if(a<100, goto2, 0);a=1;b++;if(b<100, goto2, discard=0; 

 

p       q

16     1
15     2
14     3
13     4
12     5
11     6
10     7
9      8
8     9
7    10
6    11
5    12
4    13
3    14
2    15
1    16

 Aug 9, 2020
 #2
avatar+110685 
+1

This falls out really easily if you just expand it out and add like terms.

 

\([(q+4)(p+3)]-[(q+2)(p+1)]=44\\ etc\)

 Aug 9, 2020

7 Online Users

avatar
avatar